2002
DOI: 10.1034/j.1399-3054.2002.1140315.x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar phenolic composition of European white birch during bud unfolding and leaf development

Abstract: We studied the between-tree and within-tree variation in the composition and content of foliar low-molecular-weight phenolics (LMWP) of European white birch (Betula pendula Roth) during the unfolding of vegetative buds and during early leaf development. In buds, the major groups of phenolic compounds were hydrolysable tannins and flavonoid aglycones, whereas, later during leaf development, the flavonoid glycosides accounted for most of the total LMWP. The content of total LMWP, as well as individual compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…Extraction of phenolic constituents was modified from Laitinen et al (2002) as described by Zeneli et al (2006). Briefly, wood and bark tissues were weighed (100 mg) and extracted separately with 2.5 ml of methanol (100%) using an Ultra-Turrax (IKA-WERKE, Staufen, Germany) homogenizer for 30 s, after which the sample was left for 15 min on ice.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Extraction of phenolic constituents was modified from Laitinen et al (2002) as described by Zeneli et al (2006). Briefly, wood and bark tissues were weighed (100 mg) and extracted separately with 2.5 ml of methanol (100%) using an Ultra-Turrax (IKA-WERKE, Staufen, Germany) homogenizer for 30 s, after which the sample was left for 15 min on ice.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Also, the large investment into these organs with as yet, relatively little or no return, makes them valuable to the plant (Harper 1989). Therefore, it has been suggested that chemical defenses should be most concentrated in the youngest leaves (Laitinen et al 2002).…”
Section: Ecological and Evolutionary Implicationsmentioning
confidence: 99%
“…Glandular trichomes of silver birch accumulate triterpenoids and flavonoid aglycones (e.g. 43 Valkama et al 2003), which are excreted on the surface of expanding leaves (Laitinen et al 2002, 44 Valkama et al 2004). Both types of compounds contribute to the hydrophobicity of cuticular waxes 45 (Keinänen & Julkunen-tiitto 1998), decreasing cuticular permeability to water (Barnes et al 1996).…”
mentioning
confidence: 99%